Dangerous Contenders: Election Monitors, Islamic Opposition Parties, and Terrorism. (2020) - Kavakli, Kerim Can; Kuhn, Patrick M.
Abstract: How do international observers decide whether to criticize or condone electoral fraud in a country? We argue that this decision depends on the identity of the victims of electoral fraud. A monitoring organization is more likely to overlook fraud committed against groups that are deemed dangerous by its sponsor. Based on this insight, we hypothesize that in the post-Cold War era election monitors are more tolerant of fraud against Islamic challengers, especially when Islamic movements are perceived as a threat to political stability. In support of our hypothesis, we find that outside monitors are more likely to endorse an election in countries with an Islamic opposition party and an ongoing Islamist terrorist campaign. Furthermore, we find that the effect is driven by Western monitoring organizations and becomes stronger after the September 11 attacks. Our findings provide a simple yet powerful insight: the calculus of outside observers depends not only on who they wish to see in power, but also who they want to keep from power.